Gender Wage Gap in Expectations and Realizations - Antonio Filippin; Andrea Ichino (Institute for the Study of Labor (IZA), 2003)
This paper explores the extent to which the gender wage gap is anticipated by workers' expectations. Data collected among second year students of Bocconi University convey information about their wage expectations. Detailed controls allow a clean matching with a sample of Bocconi graduates providing information about their actual wages. The evidence shows that the gender gap implied by students' expectations one year after graduation is consistent with the gender gap implied by the earnings of their elder counterparts. There is instead a misperception of the gender gap later in the career after graduation because students expect the gender gap to be roughly constant while realizations indicate an increasing gap with experience, particularly for the relatively less skilled worker. There is also evidence that the gender gap at the beginning of a career is particularly high in the most recent cohorts and lower in the previous ones. Finally, our results suggest that the careers of females are characterized by "glass ceilings" in particular at high skill levels, and by "sticky floors" at the opposite end of the skill spectrum.
Keywords: J3; J7; 330; gender wage gap; expectations; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Erwerbsverlauf; Erwartungstheorie; Experiment; Italien